2009
DOI: 10.1055/s-0029-1212011
|View full text |Cite
|
Sign up to set email alerts
|

High-dose phosphate treatment leads to hypokalemia in hypophosphatemic osteomalacia

Abstract: The mechanism of the decrease in plasma potassium induced by phosphate treatment was investigated in a 24-year-old hypertensive patient with hypophosphatemic osteomalacia, who was the youngest of four patients, belonging to a 23 number kindred of five generations. Parameters of potassium, sodium, calcium, and phosphate metabolism as well as specific renal functions have been studied in the basal state and during administration of graded doses of phosphate (500-6000 mg). Progressive hypokalemia developed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Importantly, Kasap et al showed in a case report that chronic heavy cola-flavoured drinks consumption is associated with a high risk of hypokalaemia and rhabdomyolysis leading to acute kidney injury due to its glycyrrhizin content 15. Interestingly, high phosphate intake or administration may also lead to hypokalaemia 16 17. In the UK, one can of cola-flavoured drinks (350 mL) was found to contain 5 mmol/L of phosphate (58 mg) 18.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Kasap et al showed in a case report that chronic heavy cola-flavoured drinks consumption is associated with a high risk of hypokalaemia and rhabdomyolysis leading to acute kidney injury due to its glycyrrhizin content 15. Interestingly, high phosphate intake or administration may also lead to hypokalaemia 16 17. In the UK, one can of cola-flavoured drinks (350 mL) was found to contain 5 mmol/L of phosphate (58 mg) 18.…”
Section: Discussionmentioning
confidence: 99%